Duration and Persistence in Multidimensional Deprivation: Methodology and Australian Application - Ray, R; Nicholas, A (My University, 2011)
This paper extends the recent literature on static multidimensional deprivation to propose dynamic deprivation measures that incorporate both the persistence and duration of deprivation across multiple dimensions. The paper then illustrates the usefulness of the extension by applying it to Australian panel data for the recent period, 2001-2008. The empirical application exploits the subgroup decomposability of the deprivation measures to identify the subgroups that are more deprived than others. The proposed measure is also decomposable by dimensions and is used to identify the dimensions where deprivation is more persistent. The comparison between the subgroups shows that the divide between homeowners and non-homeowners is one of the sharpest, with the latter suffering much more deprivation than the former. The results are robust to alternative schemes for weighting and aggregating the dimensions as well as to the choice of model parameters.
Economic Record
Keywords: Disadvantage -- Exclusion; Disadvantage -- Inequality; Disadvantage; Disadvantage, adversity and resilience; Disadvantage; Inequality; Exclusion; Dsiadvantage, adversity and resilience; Adversity and resilience